(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
This paper presents a method based on lightweight JavaEE for developing the web sharing system of human body data. This method is based on the feature that the body data is collected by different 3D laser body scanners from different places and the design ideal of this method is directed by UP (The Unified Software Development Process). Some open source tools (such as struts, spring and hibernate) has been introduced in this project for building the project efficiently. In Web Sharing System of Human Body Data, struts framework has been used for building the presentation layer, spring for business and logic layer, hibernate for data persistent layer. For using different data persistent strategy flexibility, the MODEL (data access object) layer has been abstracted in this method. This method not only meets the requirement of OCP(Open-Closed Principle) in computer software development, and does the best way to avoid the problems of rigidity, fragility, immobility and viscosity, but also has the features of extensibility, flexibility and pluggability in software design.